NMR spectroscopy in drug discovery and development: Evaluation of physico-chemical properties - Mire Zloh (International Association of Physical Chemists (IAPC), 2019)
Determination of physico-chemical properties of compounds is one of the corner-stones in selection of hit molecules for further progression into lead development in the modern drug discovery process. The speed of traditional analyses and limited quantities of hit molecules are obstacles for efficient acquisition of experimental data. Herein, the range of applications of quantitative nuclear magnetic resonance (NMR) spectroscopy as a fast technique used to evaluate solubility, log P and pKa are discussed.